Dionysian Embodiment: Abject Queerness in Federico García Lorca’s “Ode to Walt Whitman” - Mayron, Laura (Revista Canadiense de Estudios Hispánicos)

(untitled) (Asociación Canadiense de Hispanistas, 2022)
Federico García Lorca’s poem “Ode to Walt Whitman” from Poeta en Nueva York (1940) is well-known for its shockingly homophobic language. This article explores the discomfort and disgust surrounding queer subjectivity in the poem, specifically through images of the body. My analysis is centered on the dichotomy between Apollonian and Dionysian embodiment, a tension that reveals how Lorca’s conceptualization of queerness is linked to abjection.